The gentlewoman. (Meppel : Bruil & Van De Staaij, 2014)
Check out The Gentlewoman, a new women's magazine that will herald a new decade for female personal style and journalism of the highest quality. The Gentlewoman is launched by the acclaimed founders and editors of Fantastic Man, Jop van Bennekom and Gert Jonkers. The Gentlewoman is a top-class publication for and about women of note. The Gentlewoman will challenge the format of female personal style with a more sophisticated and in-depth oriented content. With its intelligence, quick wit and independent eye, The Gentlewoman will offer something entirely new to its readership, something the women's market has long been missing. The readers are more ambitious, confident, widely traveled and fiercely proud of their financial independence. They also have a deep love of fashion, which they display through their own personal style.
Keywords: Journalistiek -- Mode